Práticas científicas em educação física : a arqueologia do GTT escola no Congresso Brasileiro de Ciências do Esporte (1997-2009) - Carneiro, Felipe Ferreira Barros (2011)
Aimed to understand how was produced the knowledge on the school subject that, under the seal of the Colégio Brasileiro de Ciências do Esporte (CBCE), was broadcasted in the Physical Education area. The privileged fonts were the works broadcasted in the oral communications of the GTT Escola, during the Congressos Brasileiro de Ciências do Esporte (CONBRACE), occurred between 1997 and 2009. The documental corpus was compound by the 177 published texts in these congresses annals during the researched cycle. The COMBRACE is a biennial event promoted by the CBCE and represents a boundary of changes or maintenance of the institution guidelines. Understanding the annals of this congress as an editorial device for senses conformation, we also understand that the directors of this entity avail themselves of their power place to establish what deserves to be broadcast and preserved in the scientific field. The research was elaborated taking as reference the tools from the French Cultural History and the Italian Micro-history. Thus, it uses as references the proposals of Chartier (1988) on struggles of representation in the scientific authority contest in a field permeated by strategies from a power place (CERTEAU, 1994) the CBCE. The theorizations of Michel de Certeau worked as links between the History schools mobilized in this research, so that the uses and appropriations notions were also used. The methodological support was found in the evidentiary paradigm of Ginzburg (1989), from which were investigated the neglected details by what was said or not by the object. The research underscores the changes in the annals reading supports, as also in the action of the devices. Indicates that the production of knowledge in the field has attempted to follow the guidelines of the agencies for research funding. It demonstrates the uses and appropriations of the theory and methodological referential, pointing out to limits and possibilities of that production. At last, underscores the practices complexity in the scientific control that are reproduced in the CBCE instances